Tax Amnesty sebagai Instrumen Fiskal: Antara Solusi Sementara dan Ancaman - iza, amalia rochmatul (Maliki Interdisciplinary Journal, 2025)
The tax amnesty program is often utilized as a fiscal instrument by governments to boost short-term state revenue, particularly during times of fiscal pressure or low tax compliance. This study examines tax amnesty from two main perspectives: as a temporary solution capable of providing rapid fiscal injection, and as a potential threat to a fair and sustainable long-term taxation system. Using a qualitative approach through policy analysis and literature review, this article evaluates the effectiveness of tax amnesty in Indonesia and its impact on tax compliance and public trust. The findings indicate that although tax amnesty can increase revenue in the short term, it also carries the risk of creating negative incentives for compliant taxpayers and potentially undermining the integrity of the tax system. Therefore, careful consideration is required in the design and implementation of tax amnesty programs to prevent them from becoming counterproductive policy precedents in the future.